Transcription Factor WT1 and Promoter CpG Hypomethylation Coactivate HOXA10 Expression in Ovarian Cancer - Jiang, Yi; Chu, Yongli; Tang, Weiwei; Wan, Yicong; Zhang, Lin; Cheng, Wenjun (Current Pharmaceutical Design, 2014)
HOXA10 plays an important role in the body structure and development. Recently, patterns of deregulated HOX expression have been identified in various cancers. Meanwhile, WT1 is closely associated with the HOXA10 gene, which is an inducible transcription factor . We hypothesized that during the process of the ovarian cancer pathogenesis, the HOXA10 promoter CpG hypomethylation coupled with decreased WT1 expression could co-regulate HOXA10 expression. After the treatment of 5-Aza-dC, ovarian cancer cell lines(SKOV-3 and HEY) significantly increased HOXA10 expression. Transfection of HOXA10 siRNA with SKOV-3 and HEY ovarian cancer cell lines significantly downregulated HOXA10 expression but upregulated WT1 expression, compared to the control siRNA transfection. In ovarian cancer samples, the HOXA10 expression is significantly high. Nevertheless, the expression of HOXA10 is low in normal ones(P<0.05). We tried to use the method of methylation-specific PCR(MSP) to find the CpG sites, which are located in the scope of the WT1’s core-binding consensus(GCGG). In ovarian cancer samples, methylation prevalence was extremely high with the low expression of HOXA10. However, in the normal ovarian samples, the methylation prevalence was lower with the high expression of HOXA10(P<0. 05). In all samples of epithelial and normal ovarian samples collected, the WT1 expression with the promoter CpG hypomethylation of HOXA10 both contribute to the regulation of HOXA10 expression. That is to say, HOXA10 promoter methylationpositive combined with the WT1-positive result in the low expression of HOXA10. On the other hand, the HOXA10 expression was the highest in methylation-negative and WT1-negative samples.
Keywords: 5-Aza-dC